2010
DOI: 10.14507/epaa.v18n30.2010
|View full text |Cite
|
Sign up to set email alerts
|

The STEM Pipeline: The Role of Summer Research Experience in Minority Students' Graduate Aspirations

Abstract: Practical research experience has been seen as an important tool to enhance learning in STEM fields and shape commitment to science careers. Indeed, this was a prominent recommendation of the Boyer Commission. Further, there is evidence this is especially important for minority students. In this paper, we examine the role of practical research experience during the summer for talented minority undergraduates in STEM fields. We focus on the link between summer research and STEM Ph.D. program matriculation. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 32 publications
4
107
0
Order By: Relevance
“…In general, cross-sectional and longitudinal evaluations of these programs indicate that they are successful in supporting underrepresented students' interest and pursuit of STEM degrees and careers (Estrada, Woodcock, Hernandez, & Schultz, 2011; Maton & Hrabowski, 2004; Maton, Sto Domingo, Stolle-McAllister, Zimmerman, & Hrabowski, 2009; Myers & Pavel, 2011; Pender, Marcotte, Sto Domingo, & Maton, 2010; Schultz et al, 2011). Research has found that mentoring has a positive effect on sustaining interest in the sciences (Haring, 1999; Pfund, Pribbenow, Branchaw, Lauffer, & Handelsman, 2006).…”
Section: Underrepresented Students In Stemmentioning
confidence: 99%
“…In general, cross-sectional and longitudinal evaluations of these programs indicate that they are successful in supporting underrepresented students' interest and pursuit of STEM degrees and careers (Estrada, Woodcock, Hernandez, & Schultz, 2011; Maton & Hrabowski, 2004; Maton, Sto Domingo, Stolle-McAllister, Zimmerman, & Hrabowski, 2009; Myers & Pavel, 2011; Pender, Marcotte, Sto Domingo, & Maton, 2010; Schultz et al, 2011). Research has found that mentoring has a positive effect on sustaining interest in the sciences (Haring, 1999; Pfund, Pribbenow, Branchaw, Lauffer, & Handelsman, 2006).…”
Section: Underrepresented Students In Stemmentioning
confidence: 99%
“…Changing this disparity will require radical improvements in science and mathematics education as well as general academic skills across the K-12 education system. Efforts are being made to move toward positive change, including specific K-12 efforts aimed at diversity and special research programs for high school students [14],[15]. However, such change in K-12 education will at best be too slow to impact the workforce for decades.…”
mentioning
confidence: 99%
“…The importance of developing a research identity in promoting the pursuit of a PhD has been described in other science disciplines (Carlone & Johnson, 2007). Undergraduate summer research experiences also appear to change both the intention and enrollment into PhD programs in science, technology, engineering, and mathematics (STEM) disciplines (Eagan et al, 2013; Gould & Macpherson, 2003; Pender, Marcotte, Sto Domingo, & Maton, 2010). Despite the promise of summer research experiences, there is a paucity of literature describing how these programs have been implemented in nursing.…”
Section: Introductionmentioning
confidence: 99%